Analysis of Independence Ratio, Effectiveness Ratio and Growth Ratio in Assessing the Financial Performance of Bandung City Government - Nasution, Siti Nur Fadhilah; Syahrani, Annisa; Astari, Prilia; JS, Githa Amelia; Marbun, Nancy; Febyani, Vivi (Lembaga Riset Mutiara Akbar, 2025)
This study aims to analyze the financial performance of the Bandung City Government during the 2020–2024 period using the financial independence ratio, effectiveness ratio, and financial growth ratio. This analysis is important considering the strategic role of Bandung City as a center of government and economic activity in West Java Province, making the management of the Regional Revenue and Expenditure Budget (APBD) an important factor in supporting regional development. This study employs a quantitative descriptive method using secondary data in the form of Budget Realization Reports obtained from the Directorate General of Fiscal Balance (DJPK), Ministry of Finance of the Republic of Indonesia. The data were analyzed through the calculation of regional financial ratios. The results indicate that the financial independence ratio falls into the high to very high category with a delegative relationship pattern. The effectiveness ratio of local own-source revenue shows improvement but remains in the less effective category, particularly during the pandemic period. Meanwhile, revenue and expenditure growth ratios fluctuate, with declines during the pandemic and recovery in subsequent years.